1989
DOI: 10.1002/jlb.45.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Anti-ldiotypes Influence Macrophage Chemotaxis in Coxsackievirus-lnduced Murine Myocarditis

Abstract: Investigation into the mechanism(s) whereby monocytes-macrophages are mobilized to the myocardium of coxsackievirus (CVB3)-infected mice was approached by assessing the role of anti-idiotypic antibodies against specific antiviral IgG molecules. Balb/c mice preinoculated with polyclonal anti-idiotypic, syngeneic antibodies resulted in significantly decreased myocarditis after virus challenge. On the other hand, oil-induced peritoneal exudate cells obtained from virus-exposed animals demonstrated increased chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…with 108 PFU of lethally UV-irradiated CVB3 virus in Freund's complete adjuvant, followed by weekly i.p. injections for at least 6 to 8 weeks of 107 PFU of virus (20)(21)(22)(23)(24). Syngeneic BALB/cJ donors of mouse anti-Ids were immunized subcutaneously with 50 ,ug of affinity column-purified, protein A-separated, anti-CVB3-purified IgG emulsified with Freund's complete adjuvant.…”
Section: Materlils and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…with 108 PFU of lethally UV-irradiated CVB3 virus in Freund's complete adjuvant, followed by weekly i.p. injections for at least 6 to 8 weeks of 107 PFU of virus (20)(21)(22)(23)(24). Syngeneic BALB/cJ donors of mouse anti-Ids were immunized subcutaneously with 50 ,ug of affinity column-purified, protein A-separated, anti-CVB3-purified IgG emulsified with Freund's complete adjuvant.…”
Section: Materlils and Methodsmentioning
confidence: 99%
“…Previous studies from our laboratory have suggested the participation of anti-idiotypic antibodies (anti-Ids) in the induction and expression of autoimmune myocarditis induced by the enterovirus coxsackievirus B3 (CVB3) in a murine model (20). The array of immunobiological effects of polyclonal or monoclonal anti-Ids has included inhibition of myocarditis by pretreatment and/or immunization with anti-Ids in susceptible hosts (20), suppression of in vitro T-cell or splenocyte proliferative responses (22), specific modulation of macrophage chemotaxis in vitro (21), release of the lymphokine migration inhibition factor from sensitized T cells (19), and ability to bind selectively to myocyte target cell molecules and/or mimic solubilized heart-associated antigens (23). Anti-Ids were also demonstrated to induce specific, antiviral T-cell immunity (20,22,23) and stimulate secondary B-cell responses in viral or anti-Id-primed animals (20,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,4-Dinitrophenol (DNP)ovalbumin was prepared by conjugation of 0.2 ml of dinitrofluorobenzene (DNFB) to 500 mg of ovalbumin (Sigma Chemical Co., St. Louis, Mo.) as described earlier (22,23). Briefly, ovalbumin was dissolved in 100 ml of 0.85 M saline with DNFB by stirring at 25°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The method for preparing F(ab):! fragments was performed as described by Paque & Miller (1989). Briefly, purified MAb prepared in 0.1 M sodium acetate (pH 7.2) was adjusted with 2 M acetic acid to pH 4.2 and kept at 37°C.…”
Section: Animals Female Lou Rats (Harlan Sprague Dawleymentioning
confidence: 99%